1998
DOI: 10.1590/s0100-69911998000600002
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da função pulmonar em pacientes submetidos a revascularização do miocárdio sem circulação extracorpórea com derivação intraluminal

Abstract: As alterações da função pulmonar nos pacientes submetidos a cirurgias com auxílio da Circulação Extracorpórea (CEC) têm sido relatadas na literatura. O objetivo do presente estudo foi analisar a função pulmonar de um grupo de pacientes submetidos a cirurgia de revascularização do miocárdio sem o uso da CEC. Foram estudados de maneira prospectiva 23 pacientes portadores de insuficiência coronariana e submetidos a cirurgia de revascularização do miocárdio sem CEC. A idade variou de 36 a 69 anos, sendo 16 pacient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Moreover, Macchi et al [21] reported that the implement of a quick recovery after the surgical procedure allows a range of motion around the fifth day, which allows an earlier transfer of the patient to rehabilitation services. This demonstrates that the measure of deambulation ability of the patient is used by some professionals as the purpose of treatment, since this parameter represents better the individual's functional capacity [14,20,21]. Thus, one can justify, in our study, the significant negative correlation of the 6-MWT distance walked by the patient with the time of hospital stay, because it suggests that the patient who presents more deambulation ability has a functional capacity more suitable for hospital discharge, reflecting better the functionality than the lung function alone.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, Macchi et al [21] reported that the implement of a quick recovery after the surgical procedure allows a range of motion around the fifth day, which allows an earlier transfer of the patient to rehabilitation services. This demonstrates that the measure of deambulation ability of the patient is used by some professionals as the purpose of treatment, since this parameter represents better the individual's functional capacity [14,20,21]. Thus, one can justify, in our study, the significant negative correlation of the 6-MWT distance walked by the patient with the time of hospital stay, because it suggests that the patient who presents more deambulation ability has a functional capacity more suitable for hospital discharge, reflecting better the functionality than the lung function alone.…”
Section: Discussionmentioning
confidence: 89%
“…It is suggested that the reduction in forced vital capacity (FVC) and forced expiratory volume in one second (FEV 1 ) occurs by increased respiratory work and shallow breathing, due to pain and decreased chest expansion secondary to median sternotomy and thoracic manipulation, resulting in restrictive respiratory dysfunction in the postoperative period [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Neste estudo, foram encontradas reduções significativas nas variáveis CVF e VEF1, indicando um padrão restritivo, assim como estudos de , Barbosa & Carmona (2004) e Pinto et al (1998).…”
Section: Discussionunclassified
“…The School of Medical Sciences of the Santa Casa de São Paulo Hospital (FCMSCSP), among their research lines, is currently conducting studies involving the assessment of preoperative and postoperative pulmonary function tests. Many of these studies have been concluded [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%